The Planning Omnibus Law of Worker in the Perspective of Modernization and Justice: A Flash Back Review - Hono Sejati; Wieke Dewi Suryandari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
There are many overlapping regulations, and also the investment climate that is really needed to grow significantly in competition with the global world, of course to regulate this requires a regulation that can accommodate the many regulations that exist in Indonesia. Since Indonesia's independence in 1945, the government (executive and legislative) has produced laws and regulations to regulate society in the form of regeling (regulations) and beschikking (decisions). Due to the large number of overlapping regulations, many are then submitted for judicial review or testing of statutory regulations to the Constitutional Court of the Republic of Indonesia. Since the establishment of the Constitutional Court in 2003, many laws have been submitted to the Constitutional Court because they were deemed to be in conflict with the 1945 Constitution of the Republic of Indonesia. And it is true that these regulations have also been annulled by the Constitutional Court and deemed to be in conflict with the Constitution of the Republic of Indonesia.